Recursos informáticos en el proceso enseñanza – aprendizaje de la asignatura de computación del séptimo año del centro de educación inicial y escuela de educación básica “General Rumiñahui”, del cantón Yantzaza, provincia de Zamora Chinchipe, periodo 2014 – 2015. Lineamientos alternativos - Zumba Luzuriaga, Bairon Armando (2015)
This thesis refers to: RECURSOS INFORMÁTICOS EN EL PROCESO ENSEÑANZA – APRENDIZAJE DE LA ASIGNATURA DE COMPUTACIÓN DEL SÉPTIMO AÑO DEL CENTRO DE EDUCACIÓN INICIAL Y ESCUELA DE EDUCACIÓN BÁSICA “GENERAL RUMIÑAHUI”, DEL CANTÓN YANTZAZA, PROVINCIA DE ZAMORA CHINCHIPE, PERIODO 2014–2015., conducted according to the provisions of Regulation Academic Board of the National University of Loja. The central problem of the research work was: How do the computing resources in the teaching-learning process of the subject's computer seventh year of the Early Education Center and School of Basic Education "General Rumiñahui" Canton Yantzaza? He was raised as General Objective: To determine the incidence of computer resources in the teaching - learning process of the subject of computing the seventh year of the Center for Early Education and Basic Education School "General Rumiñahui" Canton Yantzaza, Zamora Chinchipe, period 2014-2015. This research was proposed based on the need to improve the teaching - learning during classroom activities for students of basic education, starting with the search for partner issues - education that affect the normal functioning of daily activities in class , being way you could identify that there were problems in the use of computing resources are there teachers in the subject's computer center for early childhood education and basic education school "General Rumiñahui" Canton Yantzaza. The methods used were scientific, inductive/deductive, statistical methodology that was used to collect information necessary for the development of research, with the help of some techniques and instruments such as direct observation, classroom activities which It helped to confirm the application of computing resources in classroom activities, the interview was applied to teachers of the subject of computing and survey students to obtain information justifying this research. It is concluded that: 86% of students surveyed say they would be different classes if they used educational software or website for classroom activities, 64%, believe that modern computing resources help improve the knowledge of students also said that if the teacher uses resources via the web, such as blogs, wiki, email, etc.